Bioanalysis Young Investigator: Pan Deng. (May 2012) - Deng, Pan; Zhong, Dafang
Supervisor's supporting comments I would like to nominate Pan Deng for the Bioanalysis Young Investigator Award 2012. Her research projects include developing LC–MS/MS methods for the quantification of small and large molecules to support drug pharmacokinetic studies. During her PhD training in my laboratory, she has gained much experience in developing sensitive LC–MS/MS methods for the measurement of various compounds, especially polar analytes, and published several research and review papers. As part of her PhD project, she also investigated the metabolism of drugs utilizing UPLC-Q/TOF MS. Her efforts in studying drug metabolism study have led to the finding of new metabolites, and unveiling the metabolic pathways of several new drug candidates. She is currently expanding her research into the area of drug toxicity. Hopefully this Young Investigator Award will encourage Deng to have greater achievements.